A Modern View on Forward Security. (24th August 2020) - Boyd, Colin; Gellert, Kai
Abstract: Forward security ensures that compromise of entities today does not impact the security of cryptographic primitives employed in the past. Such a form of security is regarded as increasingly important in the modern world due to the existence of adversaries with mass storage capabilities and powerful infiltration abilities. Although the idea of forward security has been known for over 30 years, current understanding of what it really should mean is limited due to the prevalence of new techniques and inconsistent terminology. We survey existing methods for achieving forward security for different cryptographic primitives and propose new definitions and terminology aimed at a unified treatment of the notion.